STRATEGI PEMERINTAH DAERAH DALAM MENJAGA KEAMANAN DAN KETERTIBAN MASYARAKAT - LELET, NINA ELISABET; LALOMA, ALDEN; LONDA, VERY (Sam Ratulangi University, 2022)
This study aims to determine and analyze the Strategy of the National Unity and Regional Political Agencyof North Sulawesi Province in Maintaining Public Security and Order. This research uses descriptivequalitative research method with SWOT data analysis technique. SWOT analysis is carried out using theInternal Factory Analysis Summary (IFAS) and External Factory Analysis Summary (EFAS) matrices toshow the current position of the organization. From the data results, it is known that the National Unity andRegional Political Agency of North Sulawesi Province is currently in a position between the Opportunityand Strength axes, namely in Quadrant I (S-O Strategy). Which means that the National Unity and RegionalPolitical Agency of North Sulawesi Province has the opportunity and strength, so that it can direct the entireinternal potential of the organization to take advantage of existing opportunities. The strategy that must beapplied in this condition is to support an aggressive growth policy. Based on the results of the SWOT matrixanalysis, six strategic issues were determined, then based on the Litmust Test, there were four strategicissues and two fairly strategic issues.Keywords: Strategy, Local Government, Security and Public Order